The Implementation of Multicultural- Based Sociology Learning in Senior High School - Rochana, Totok (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
This study examines the implementation of multicultural-based sociology learning in senior high school. The objectives of this study are: (1) To describe the sociology learning that is carried out currently; and (2) to describe the implementation of multicultural-based sociology learning. This study employed a qualitative approach to produce a description and analysis of findings. The subjects of the study were sociology teachers in Kendal Regency. The type of data collection was both in the form of quantitative data and qualitative data. The data were collected using observation and interview guidelines. Data analysis used descriptive qualitative analysis with interactive techniques. The current implementation of sociology learning is based on the learning objectives of sociology, namely to develop sociology knowledge and practice to improve students’ social skills. Based on the objectives of sociology learning, it influences the learning approaches, models, methods, media and resources, and assessment. The implementation of multicultural-based sociology learning is based on the goal of multicultural learning. The learning is addressed as an effort to develop students' ability to view different cultures and to be positive towards cultural, racial, and ethnic differences. Based on these learning objectives, the implementation of sociology learning differs in terms of learning approaches, models, methods, and assessments.